2015
DOI: 10.3389/fpsyg.2015.00235
|View full text |Cite
|
Sign up to set email alerts
|

Women are underrepresented in fields where success is believed to require brilliance

Abstract: Women’s underrepresentation in science, technology, engineering, and mathematics (STEM) fields is a prominent concern in our society and many others. Closer inspection of this phenomenon reveals a more nuanced picture, however, with women achieving parity with men at the Ph.D. level in certain STEM fields, while also being underrepresented in some non-STEM fields. It is important to consider and provide an account of this field-by-field variability. The field-specific ability beliefs (FAB) hypothesis aims to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
175
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(191 citation statements)
references
References 38 publications
10
175
1
5
Order By: Relevance
“…In addition, the models include various permutations of the following GRE-based variables: the quantitative score, the verbal score, the analytical writing score, the quantitative:verbal ratio score, and the quantitative−verbal difference score. Adjusting for quantitative GRE scores provides a conservative test of our hypothesis, as academics and nonacademics alike believe that success in mathematics depends largely on raw ability (1,8). Thus, young men and women's quantitative GRE scores may already reflect the influence of mathematics-specific ability beliefs, so adjusting for these scores in our analyses may underestimate the true impact of ability beliefs on gender gaps in representation.…”
mentioning
confidence: 98%
“…In addition, the models include various permutations of the following GRE-based variables: the quantitative score, the verbal score, the analytical writing score, the quantitative:verbal ratio score, and the quantitative−verbal difference score. Adjusting for quantitative GRE scores provides a conservative test of our hypothesis, as academics and nonacademics alike believe that success in mathematics depends largely on raw ability (1,8). Thus, young men and women's quantitative GRE scores may already reflect the influence of mathematics-specific ability beliefs, so adjusting for these scores in our analyses may underestimate the true impact of ability beliefs on gender gaps in representation.…”
mentioning
confidence: 98%
“…Research results indicate that the gender stereotype whereby men are better at mathematics than women is formed in the early years of the education system (Cvencek, Meltzoff and Greenwald, 2011). The belief on which this stereotype is based is that women are innately worse endowed to perform tasks associated with social success (Meyer et al, 2015;Paustian-Underdahl, Walker & Woehr, 2014). It has been demonstrated experimentally that an act as simple as requesting innate talent rather than commitment and dedication when advertising an employment or educational opening prompts a significant decrease in women's motivation to present themselves as candidates (Cimpian, Bian and Leslie, 2014).…”
Section: Background and Theoretical Foundationmentioning
confidence: 96%
“…All of these comprise dimensions of the fundamental construct, which is none other than the patriarchal organisation of society and the corresponding gender socialisation, as highlighted when the interviewed women themselves reported that some university degrees and career opportunities were "entirely populated by women". This illustrates the continuing validity of the argument put forward by Meyer et al (2015), according to which gender socialisation has created stereotypes whereby women are perceived as having less training and capacity to perform certain jobs regarded as male and geared to success and excellence. This way of thinking was exemplified in one of the statements obtained, according to which women are unable to separate family from work, which could give the impression that they cannot put aside family problems or responsibilities, with the consequent negative impact on their professional performance.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Las creencias interiorizadas según las cuales la mujer está poco capacitada para ejercer determinadas tareas, que Meyer, Cimpian y Leslie (2015) han denominado "Creencias de las capacidades específicas de campo", se asume como la causa de la baja representación de las mujeres en los ámbitos académicos y laborales relacionados con la ciencia, la ingeniería y las matemáticas. La creencia que sustenta el estereotipo es que las mujeres tienen, de forma innata, menos capacidad para comprometerse con tareas orientadas al éxito social (Meyer et al, 2015). De hecho, un experimento llevado a cabo por Cimpian, Bian y Leslie (2014) ha constatado que el simple hecho de solicitar en una oferta de empleo o educativa el requisito de tener talento (frente a dedicación) es suficiente para que la motivación de las mujeres y chicas jóvenes disminuya significativamente.…”
Section: Introductionunclassified